Pulmonary Hypertension in ESRD Patients - Anjum, Roshina; Fatma, Zahra; Saleem, Sidra; Afzal, Aurangzeb (Pakistan Journal of Kidney Diseases, 2021)
Dialysis patients are at risk for development of pulmonary hypertension (PH). Although multifactorial, the increased risk is partly due to the presence of an arteriovenous (AV) access(1)and is strongly associated with an enlarged left atrium and poor prognosis .Multiple studies have been done to prove direct relationship between ESRD and PH. This review is based on a search of Medline and citation lists of relevant publications. The main goal of this review is to highlight the magnitude of the problem and need of early screening and management of PH in end stage renal disease (ESRD) patients so that morbidity and mortality can be reduced.